Anaerobic and aerobic energy system contribution to 400-m flat and 400-m hurdles track running - Zouhal, H,; Jabbour, G.; Jacob, C.; Duvigneau, D.; Botcazou, M.; Ben Abderrahaman, A.; Prioux, J.; Moussa, E. (The Journal of Strength and Conditioning Research, 2010)
The present study was designed to determine the aerobic and anaerobic energy contributions to 400-m Flat (400mF) and 400-m hurdles (400mH) using the accumulated oxygen deficit method. Six nationally ranked athletes, specializing in 400mH and familiar with 400mF volunteered to participate in this study. All the participants performed 3 track-running sessions. The first session determine the maximal oxygen uptake and maximal aerobic speed using lightweight ambulatory respiratory gas exchange measurements (o2000, Medical Graphics). The second and third tests consist of a 400mF and a 400mH performed on the track in a randomized counterbalanced order. Accumulated oxygen deficit determined during the 400mF was significantly higher than that determined during the 400mH (65.0 ± 10.0 ml/kg vs. 44.1 ± 7.4 ml/kg, p < 0.05). Thus, the aerobic contribution calculated was significantly higher during the 400mH compared to during the 400mF (43.0 ± 2.0 vs. 37.4 ± 2.7%, p < 0.05, respectively). These results strongly suggest that the aerobic contribution is greater during a 400mH compared to during a 400mF. Thus, this study provides a scientific rationale behind the coaches' practice and contributes to a better understanding of the differences between 400mF and 400mH. Then, the coaches must propose different training programs for both 400mF and 400mH runners.